2019
DOI: 10.3389/fpls.2019.00513
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing and Comparative Genomic Analysis Reveal Allelic Variations Unique to a Purple Colored Rice Landrace (Oryza sativa ssp. indica cv. Purpleputtu)

Abstract: Purpleputtu (Oryza sativa ssp. indica cv. Purpleputtu) is a unique rice landrace from southern India that exhibits predominantly purple color. This study reports the underlying genetic complexity of the trait, associated domestication and dedomestication processes during its coevolution with present day cultivars. Along-with genome level allelic variations in the entire gene repertoire associated with the purple, red coloration of grain and other plant parts. Comparative genomic analysis using 'a panel of 108 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…Several authors have attempted to correlate sequence variants of a number of regulatory genes, e.g., C1 and OSB2, with phenotypic variation in rice grain pigmentation (Sakulsingharoj et al, 2016;Rachasima et al, 2017;Sun et al, 2018). Lachagari et al (2019) conducted comparative genomics in 108 rice lines and identified novel allelic variants in a number of genes belonging to the flavonoid pathway, cytokinins glucoside, and betanidin degradation biosynthesis that were associated with purple pigmentation. Although a number of genes responsible for grain pigmentation have already been identified ( Table 2), there is still a possibility that additional genes and variants thereof, remain to be discovered.…”
Section: Regulatory Cascade Influencing Purple Rice Colormentioning
confidence: 99%
“…Several authors have attempted to correlate sequence variants of a number of regulatory genes, e.g., C1 and OSB2, with phenotypic variation in rice grain pigmentation (Sakulsingharoj et al, 2016;Rachasima et al, 2017;Sun et al, 2018). Lachagari et al (2019) conducted comparative genomics in 108 rice lines and identified novel allelic variants in a number of genes belonging to the flavonoid pathway, cytokinins glucoside, and betanidin degradation biosynthesis that were associated with purple pigmentation. Although a number of genes responsible for grain pigmentation have already been identified ( Table 2), there is still a possibility that additional genes and variants thereof, remain to be discovered.…”
Section: Regulatory Cascade Influencing Purple Rice Colormentioning
confidence: 99%
“…HTS systems offer extremely cost-effective sequencing generation for large amounts of data. Therefore, HTS systems are already used in genotyping projects that employ different strategies to find polymorphisms, such as genotyping by sequencing [ 54 ], capturing strategies [ 55 , 56 , 57 ], or the shotgun sequencing of entire genomes [ 58 ]. Microsatellites are multiallelic markers, which makes them ideal for the management of plant germplasm.…”
Section: Resultsmentioning
confidence: 99%
“…The development of NGS technology can compensate for these deficiencies and promote the development of plant molecular breeding [31,32,33,34]. BSA mixed population separation analysis is often used in whole-genome resequencing, and two groups with extreme traits are mainly sequenced by mixed pool.…”
Section: Discussionmentioning
confidence: 99%